An example of the conservation of “Dede Tombs”, the symbols of Alevi- Bektashi culture Isparta – İsmail Dede Tomb - Gökarslan, Ayşe Betül; Köse, Duygu (Journal of Alevism-Bektashism Studies, 2023)
Isparta hosted the Alevi - Bektashi Culture and has many Dede Tombs built within the framework of the Veli Cult. İsmail Dede Tomb, located in Yakaören Village of Isparta Provincial Center, which is one of the settlements with Alevi-Bektashi culture such as Gümüşgün, Aliköy and Uluğbey, is one of these tombs. Since there is no foundation charter or inscription, the exact date the building was built is unknown. Although it is known that the tomb of Şeyh İsmail Efendi is dated 1617 A.D. (H. 1026) and the tombstone belonging to the grandfather’s assistant in the courtyard is dated 1891 M. (H. 1309), the plan type of the building, its façade architecture and the materials and structural techniques used in its construction indicate the date of construction of the building. shows that it does not coincide with these dates. The tomb, which is thought to have been repaired or largely reconstructed in the 1960s, needs to be restored while preserving its originality. However, deep cracks have formed in the body walls as a result of both the deterioration caused by faulty repairs and the direct contact of adverse climatic conditions with the structure (insufficient top cover and drainage systems in the garden). In particular, the movement of the stones on the northern façade of the building indicates that the building is in danger of collapsing towards the north at any moment, and it urgently needs comprehensive repairs.Tomb restoration works initiated within the scope of Isparta Governorship are carried out by the Provincial Directorate of Culture and Tourism. The Provincial Directorate of Culture and Tourism consults with relevant institutions and organizations and assigns the preparation of projects in the most comfortable and easy way for the public benefit to restoration expert architects. The survey, restitution and restoration projects of the Ismail Dede Tomb were also drawn by authors who made an agreement with the Provincial Directorate of Culture. The spatial and structural problems of the building were mentioned, and then the intervention decisions were given to eliminate these problems and to ensure that the building could continue its current function as close to the original space as possible. It is aimed to transfer the Ismail Dede Tomb, one of the few Dede Tombs in this region where the Alevi - Bektashi people live, to future generations with its original function and structural elements, and to contribute to the literature on the conservation of cultural heritage.
Keywords: Conservation and Restoration; Alevism; Bektashism; Architecture of Tomb; İsmail Dede Tomb